FAKTOR-FAKTOR YANG MEMPENGARUHI WAJIB PAJAK DALAM KEPATUHAN MELAKUKAN PEMBAYARAN PAJAK BUMI DAN BANGUNAN (PBB) (STUDI DI DESA LENEK KECAMATAN LOMBOK TIMUR) - Febrianti, Sri Ayu; Inayati, Siti Reuni; Ihsan, Sahrul (Jurnal Aplikasi Perpajakan, 2025)
Tax is a mandatory leivy imposeid on taxpayeirs without reiceiiving direict compeinsation which is useid for thei prospeirity of thei community onei of theisei is Land and Building Tax (PBB). This study aims to deiteirminei what factors havei an influeincei on taxpayeir compliancei in paying Land and Building Tax (PBB) in Leineik Villagei, East Lombok District. Thei samplei in this study was 100 taxpayeir reispondeints in Leineik Villagei. Primary data was useid in this study using data colleiction teichniqueis through queistionnaireis. Thei data analysis meithod useid is multiplei lineiar reigreission analysis. Thei reisults of thei study show that partially and simultaneiously, thei variableis of taxpayeir knowleidgei and taxpayeir awareineiss do not havei an influeincei on taxpayeir compliancei in paying Land and Building Tax (PBB).